Data activism and social change - Gutiérrez, Miren (Palgrave Macmillan, 2018)
This book efficiently contributes to our understanding of the interplay between data, technology and communicative practice on the one hand, and democratic participation on the other. It addresses the emergence of proactive data activism, a new sociotechnical phenomenon in the field of action that arises as a reaction to massive datafication, and makes affirmative use of data for advocacy and social change. By blending empirical observation and in-depth qualitative interviews, Gutiérrez brings to the fore a debate about the social uses of the data infrastructure and examines precisely how people employ it, in combination with other technologies, to collaborate and act for social change.
Keywords: Changement social; Collaboration; Data collaboratives; Réservé UdeM; Technologie